Neonatal near miss and associated factors among neonates delivered at East Gojjam zone public health hospitals, Northwest Ethiopia - Melesse Tesfa; Tadesse Yirga Akalu; Bewket Yeserah Aynalem (Scientific Reports)
Abstract Neonatal mortality and morbidity is a significant public health issue globally, particularly in low-income countries including Ethiopia. This study aimed to determine the proportion and associated factors of neonatal near misses among newborns delivered at public hospitals in the East Gojjam zone of Northwest Ethiopia. A facility-based cross-sectional study was conducted from April 21 to June 20, 2023, among 560 newborns and their mothers in randomly selected five public hospitals. Data was collected using an interviewer-administered questionnaire, medical record review, and a standard checklist with a systematic random sampling technique in each proportionally allocated hospital. The data was entered using 4.6 Epi-data software and exported to SPSS version 25. Bivariable and multivariable logistic regression analyses were performed using a backward stepwise approach method, and statistical significance was declared at a 95% confidence interval with a p-value < 0.05. A total of 552 participants responded to the study, with a response rate of 98.6%. The prevalence of neonatal near miss was 41.3% with a 95% confidence interval of 37.1–45.3. Unplanned pregnancy (AOR = 4.91, 95% CI: 2.43–9.94), current obstetric complications at birth (AOR = 5.48, 95% CI: 2.92–10.27), pregnancy-induced hypertension (AOR = 2.75, 95% CI: 1.23–6.12), premature rupture of membrane (AOR = 3.40, 95% CI: 1.71–6.78), mother referred from other healthcare facilities (AOR = 7.12, 95% CI: 4.01–12.63), delivered on-duty time (AOR = 5.04, 95% CI: 2.94–8.65), less than three ultrasound scans (AOR = 3.71, 95% CI: 2.11–6.53), and no ultrasound scan (AOR = 9.44, 95% CI: 2.55–34.99) were significantly associated with neonatal near miss. The prevalence of neonatal near-misses was 41.3% (95% CI: 37.1%, 45.3%). Unplanned pregnancy, obstetric complications at birth, ultrasound scan, premature rupture of membrane, pregnancy-induced hypertension, and mothers referred from other healthcare facilities, and delivered on-duty time were significant factors associated with neonatal near misses.